Peculiarities of interspousal relations in infertile marriages - V. A. Stepanova (Вестник университета)
The issue of marital relations in infertile marriages that experience difficulties in conceiving a child for unknown (unspecified) reasons has been analyzed. In the study aimed at identifying the peculiarities of interspousal relations, 312 married couples with women having unspecified infertility took part. The degree of satisfaction of men and women with marriage, differences in assessments of their well-being (methodology of V.V. Stolin, G.P. Butenko and T.L. Romanova), features of communication between spouses (questionnaire of Yu.Ye. Aleshina, L.Ya. Gozman, E.M. Dubovskaya), type of communication system in family (methodology of T.I. Bonkalo), and dyadic coping strategies of spouses (scale of M. Bowman in the adaptation of E.V. Kuftyak) have been studied. It has been revealed that interspousal relations in infertile marriages are quite diverse and changeable. At the same time, the characteristics similar for the majority of married couples are a decrease in the ability of spouses to create a comfortable atmosphere in interpersonal communications and to establish psychological contact with each other, indirect type of communication system, and lack of unity of views on the ideal marriage and interpersonal relations. In such families a wide variety of relationships can be formed depending on the types of their personality, conditioned by the peculiarities of childhood experience and perception of the parental family. It has been concluded that it is expedient and necessary to conduct further research aimed at identifying the personality types of women with psychological infertility and the factors determining the formation of their respective typological features in order to clarify the regularities of their interaction with their spouses.